A new risk factor for predicting stroke in patients with atrial fibrillation: morning blood pressure surge. Issue 2 (23rd April 2023) - Gorcan, Ayberk; Argan, Onur; Avci, Eyup; Kiris, Tuncay; Safak, Ozgen; Yildirim, Seda Tarik; Yildirim, Elcim; Lutfi Kisacik, Halil; Kadi, Hasan
Abstract : Background: Stroke, the most feared complication in patients with atrial fibrillation (AF), is still an important cause of mortality and morbidity. In our study, we aimed to investigate the frequency of stroke and related parameters in patients with atrial fibrillation, for whom 24-h ambulatory blood pressure monitoring (ABPM) was performed. Method: A total of 282 patients with permanent AF were included in this study. 24-h ABPM was performed in all patients. Morning blood pressure surge (MBPS) was defined as the difference between the mean SBP in the first 2 h after awakening and the lowest blood pressure (BP) at night. We evaluated parameters associated with stroke in patients with atrial fibrillation using univariate and multivariate Cox regression analysis. Result: Patients were followed for 19 ± 9.3 months and 22 ischemic strokes were detected during the follow-up period. Also, strokes were significantly lower in atrial fibrillation patients with a dipper BP pattern, whereas strokes were significantly higher in atrial fibrillation patients with a reverse-dipper BP pattern. In multivariate analysis, a history of hypertension ( P = 0.020), BP pattern ( P < 0.001) and MBPS ( P < 0.001) were found to be significantly related to stroke. MBPS levels >32.5 mmHg predicted stroke with a sensitivity of 77% and a specificity of 60% (AUC, 0.741; 95% CI, 0.647–0.834; P < 0.001). Conclusion: MBPS, BP pattern and presence of hypertension as an independent risk factor in predicting stroke in patients with atrial fibrillation. The reduction of the MBPS may be a new therapeutic target for preventing stroke.